STRATEGI PEMBIASAAN KARAKTER BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUS - Fauziah, Siti Bustani; Mahmudah, Fitri Nur; Susatya, Edhy (Graduate Program Magister Manajemen Pendidikan, 2020)
Character education is the main pillar in creating a person?s character through education, both formal and informal education. This study aims to find out the habituation and the usual activities conducted by homeroom teachers for character development of students with special needs in Sekolah Luar Biasa Negeri Pembina Yogyakarta. The results showed many activities taken by the guardians at the school in the developing character of students. Some of the activities were flag ceremonies, cooperation, activities that instill values of integrity, as well as nationalist and religious activities. Also, there are habituation activities conducted by the homeroom teacher in developing the character of students with special needs. Among others are independencies, lining up before entering the classroom, knocking on the door, and greeting before entering the room, tidying up the equipment after use, immediately apologizing if making a mistake, and respecting religious differences. The implication in the character formation and development of students with special needs that the habituation should be done continuously to facilitate the implementation in the society.